2011
DOI: 10.1007/s00508-011-1592-5
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental resection for subfascial extremity soft tissue sarcoma and quality of life in long-term survivors

Abstract: The surgical management of soft tissue sarcoma has changed over the past years, resulting in an interdisciplinary multimodal approach and limb-preserving treatment modalities. From 464 consecutive patients with a soft tissue sarcoma (STS) of an extremity, a compartmental resection was performed in 82 patients, usually for primary subfascial large tumors. Postoperative quality of life was evaluated using the EORTC Score C30. In our study population, 52% of STS was poorly differentiated, 32% moderately, and 16% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Our results accentuate the need for a radical surgical approach to the primary tumor; for all subcutaneous tumors a radical resection achieving three-dimensional tumor-free resection margins may be associated with improved freedom of local recurrence [19]. The prognostic influence of initial optimal resection on local resection in spite of initial re-excision was demonstrated in a recent study that supports the demand for treatment of STS in specialized centers [20]. The observation by Rydholm and Gustafson Our multivariate analysis revealed that the size of the primary tumor is the single risk factor of local recurrence.…”
Section: Discussionsupporting
confidence: 60%
“…Our results accentuate the need for a radical surgical approach to the primary tumor; for all subcutaneous tumors a radical resection achieving three-dimensional tumor-free resection margins may be associated with improved freedom of local recurrence [19]. The prognostic influence of initial optimal resection on local resection in spite of initial re-excision was demonstrated in a recent study that supports the demand for treatment of STS in specialized centers [20]. The observation by Rydholm and Gustafson Our multivariate analysis revealed that the size of the primary tumor is the single risk factor of local recurrence.…”
Section: Discussionsupporting
confidence: 60%
“…Patients’ QoL (investigated with RAND-36) after hyperthermic isolated limb perfusion for locally advanced extremity soft tissue sarcoma was significantly worse in physical functioning comparing to the healthy Dutch population [8]. Investigations of QoL after compartimental resection for subfascial extremity soft tissue sarcoma (using EORTC Score C30) showed decreased QoL scores in all dimensions, compared to a normal population [31]. Reichardt et al and Coens et al investigated the HRQoL of patients with soft tissue sarcoma and chemotherapy [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Even general information on HRQoL in advanced STS after first‐line treatment is scarce: only 6 randomized trials (this study and 5 phase 2 trials) have been published since 1980 . HRQoL results are more common in extremity STS in patients with early/localized disease . For this population, surgical options and impairment in physical functioning are obviously the dominant issues, as is the lack of patient input in decisions regarding treatment .…”
Section: Discussionmentioning
confidence: 99%